2011
DOI: 10.1007/s10439-011-0386-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Animal Models for Concussion and Serious Brain Injury

Abstract: Three animal models were evaluated in this study involving head impacts of the rat, including the Marmarou drop-weight and two momentum-exchange techniques. In series 1, 36 Wistar rats were hit on the side of the free-moving head using Marmarou's 450 g impact mass at 4.4, 5.4, and 6.3 m/s. Head acceleration was measured and injuries were observed. The 6.3-m/s side impact resulted in no deaths, no skull fractures, infrequent contusions, and some injuries consistent with diffuse axonal injury. In series 2, 57 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…We selectively used three traditional fall heights, which were obtained from conditions identical to those in the original impact acceleration model by Marmarou [4, 5]. The induction of behavioral and neuropathological changes in our study is similar to that of earlier studies that used identical or similar models [17, 18, 23]. We observed that the neurological scores and functional beam balance varied with impact force and acceleration; an impact height of less than 1 m produced no or mild impaired functional behaviors, whereas increasing the impact height to 1.5 and 2.0 m significantly increased impaired functional behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…We selectively used three traditional fall heights, which were obtained from conditions identical to those in the original impact acceleration model by Marmarou [4, 5]. The induction of behavioral and neuropathological changes in our study is similar to that of earlier studies that used identical or similar models [17, 18, 23]. We observed that the neurological scores and functional beam balance varied with impact force and acceleration; an impact height of less than 1 m produced no or mild impaired functional behaviors, whereas increasing the impact height to 1.5 and 2.0 m significantly increased impaired functional behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…Methods to dissipate energy across the skull and allow greater skull movement upon impact by using flexible platforms can shift the injury type from a more focal to a more diffuse pattern. In the Marmarou method, for example, the rodent’s head is supported on a thick block of foam or gel that allows partial head acceleration, which causes moderate to severe brain injury with DAI, which is characterized by prominent amyloid precursor protein (APP) immunostaining (Foda and Marmarou, 1994; Marmarou et al, 1994; Viano et al, 2012). Recently, Kane et al described a new murine CHI model (Kane et al, 2012) characterized by a completely unrestrained head and body.…”
Section: Closed Head Injury Models Of Tbimentioning
confidence: 99%
“…To date, concussion research has primarily focused on the high school, college, and professional levels of play. The NFL has conducted extensive concussion research, where select impacts were reconstructed using instru mented crash test dummies to further understand the impact con ditions and biomechanics associated with concussions [12][13][14][15][16][17]. However, this work was mostly limited to reconstructions of open-field impacts in which one player sustained a concussion, which resulted in a biased dataset that was too heavily weighted toward concussion for appropriate risk analyses.…”
Section: Introductionmentioning
confidence: 99%